The earth's magnetic interior - Petrovský, Eduard; Ivers, David; Harinarayana, T.; Herrero-Berve, Emilio (IAGA special sopron book series, 2011)
This volume combines review and solicited contributions, related to scientific studies of Division I of IAGA presented recently at its Scientific Assembly in Sopron in 2009. The book is aimed at intermediate to advanced readers dealing with the Earth's magnetic field generation, its historical records in rocks and geological formations - including links to geodynamics and magnetic dating, with magnetic carriers in earth materials, electromagnetic induction and conductivity studies of the Earth interior with environmental applications of rock magnetism and electromagnetism.